2012
DOI: 10.1111/ctr.12013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic renal outcome after living donor liver transplantation

Abstract: Chronic kidney disease (CKD) is one of the common complications after deceased donor liver transplantation. Although the worldwide pressing shortage in deceased donors has directed attention to living donor liver transplantation (LDLT), LDLT cohort data focusing on chronic renal dysfunction is limited. A total of 280 adult LDLT recipients (median 49 yr, 156 men) at the University of Tokyo hospital between 1996 and 2006 were reviewed. A total of 224 pre-transplant liver failure patients (80.0%) showed an estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Patients with a higher pre‐transplant eGFR appear to have a similar decline in both DDLT and LDLT groups. Similar findings were noted by Nishi et al, who demonstrated that LDLTs have a more rapid deterioration of renal function, especially in the first year . A study from Toronto, specifically looking at patients who had undergone LT for hepato‐renal syndrome, showed similar creatinine levels in between the two groups at five yr, but the rate of eGFR decline was not reported .…”
Section: Discussionsupporting
confidence: 81%
“…Patients with a higher pre‐transplant eGFR appear to have a similar decline in both DDLT and LDLT groups. Similar findings were noted by Nishi et al, who demonstrated that LDLTs have a more rapid deterioration of renal function, especially in the first year . A study from Toronto, specifically looking at patients who had undergone LT for hepato‐renal syndrome, showed similar creatinine levels in between the two groups at five yr, but the rate of eGFR decline was not reported .…”
Section: Discussionsupporting
confidence: 81%
“…A single-center retrospective analysis of 202 primary liver transplants has reported a doubling of the risk for both cardiovascular events and cardiovascular mortality in patients with eGFR <60 mL/min/1.73 m 2 [ 6 ]. With 25–50% of patients showing moderate or severe renal dysfunction after liver transplantation [ 6 , 10 , 11 ], the impact of renal function on cardiovascular events is highly relevant. However, prospective studies of the association between renal function and cardiovascular events in liver transplant patients have hitherto been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported a significant relationship between pre‐transplant serum creatinine and post‐transplant CKD . In a previous study, we observed that patients with normal insulin clearance and normal serum creatinine can have severe histological injuries, which suggests that impaired kidney function can be delayed compared to histological lesions .…”
Section: Discussionmentioning
confidence: 78%